If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x^9=-3x-12+5x
We move all terms to the left:
5x^9-(-3x-12+5x)=0
We do not support expression: x^9
| 39y+7y^2=18 | | 4/16x-261=1/x^2 | | 10/x=5/2x+45 | | -18u-18=-2u-12 | | 4(-4+x)=5x+1/4 | | 3x+5+5x-18=90 | | m-6=-11+2m | | 8b+28=-4+4b+12 | | √-8+6x=x | | (2/3)z=41/4 | | -7=2x=-45x | | 6=((2/3)x) | | 7n+12=(-23) | | g=19-21 | | √8-6x=x | | 243=27t | | 16n+-16=4n+2 | | 4=6+f | | 0=((2/3)x)-6 | | -7=2x+-4=5x | | (x-4)+x=150 | | -7x+5=8x-25+ | | 3/2=6/((x-3)^2) | | -9x+11-x-2x-33=122 | | 48+2x=x2 | | 4.9+1.3n=1.65 | | x+12/6=7 | | 60/2x=8 | | (2x+1)/3+2=x | | 6=-9x-12 | | 8j-9-3j=+2 | | 17-t=23 |